(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Arab women occupied their aesthetic expressions, and this was evident in poetry and prose alike, which showed the richness of Arab aesthetic culture on several levels. . There were many aesthetic expressions among Arabs in describing women, such as beauty, navigation, sweetness, morning, tenderness, grace, vitality, splendor...etc. This article depicts images of the Arab culture’s aesthetic beauty in particular, as the book Women’s News mentioned more than a beautiful description of women. The research has taken the descriptive approach as a procedural starting point that helps it in extrapolating the aesthetic texts inherent in the prose heritage books, using the tools of cultural criticism, and then responding to observation, analysis and discussion of these propositions, reading them aesthetically, and the extent to which these ideas are related to society and culture.